Endophytic Aspergillii and Penicillii from medicinal plants: a focus on antimicrobial and multidrug resistant pathogens inhibitory activity - Jendri Mamangkey; Lucas William Mendes; Apon Zaenal Mustopa; Adrian Hartanto (BioTechnologia, 2024)
The rise of multidrug resistance among microorganisms, where they develop resistance against formerly efficacious drugs, has led to increased disease prevalence and mortality rates, posing a growing challenge. Globally, antibiotic resistance has made a significant impact, causing millions of fatalities each year. Endophytic fungi have gained considerable attention in research due to their potential to produce a wide variety of secondary metabolites, including natural substances with antimicrobial capabilities. The genera Aspergillus and Penicillium stand out as the most prevalent species of endophytic fungi. Filamentous fungi, such as these are responsible for the production of 45% of known microbial metabolites. This review focuses on exploring the bioactive substances produced by endophytic fungi from these two genera, particularly in conjunction with medicinal plants. Emphasis is placed on their antimicrobial activity and their ability to inhibit multidrug-resistant pathogens. As the need for alternative treatments to combat drug-resistant infections continues to grow, endophytic fungi have the potential to provide a valuable source of bioactive molecules for medical applications.